Neonatal mortality: an invisible and marginalised trauma - Mats Målqvist (Taylor & Francis Group, 2011)
Neonatal mortality is a major health problem in low and middle income countries and the rate of improvement of newborn survival is slow. This article is a review of the PhD thesis by Mats Målqvist, titled ‘Who can save the unseen – Studies on neonatal mortality in Quang Ninh province, Vietnam,’ from Uppsala University. The thesis aims to investigate structural barriers to newborn health improvements and determinants of neonatal death. The findings reveal a severe under-reporting of neonatal deaths in the official health statistics in Quang Ninh province in northern Vietnam. The neonatal mortality rate (NMR) found was four times higher than what was reported to the Ministry of Health. This underestimation of the problem inhibits adequate interventions and efforts to improve the survival of newborns and highlights the invisibility of this vulnerable group.The findings of the thesis also point at an inequity in survival chances based on ethnicity of the mother. Newborns of ethnic minority mothers were at a twofold risk of dying within the first 4 weeks of life compared to their peers belonging to the hegemonic group of Kinh (OR 2.08, 95% CI: 1.39–3.10). This increased risk was independent of maternal education and household economic status. Neonatal mortality was also associated with home deliveries, non-attendance to antenatal care and distance to the health care facilities. However, ethnic minority mothers still had an increased risk of experiencing a neonatal death even if they attended antenatal care, delivered at, or lived close to a health facility. This example of ethnic inequity highlights the importance to target those most in need.This article has been commented on by Zulfiqar A Bhutta. Please follow this link http://www.globalhealthaction.net/index.php/gha/article/view/6360 – to read his Commentary.